2018
DOI: 10.21859/ijb.1454
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing in Vitro Organogenesis of Chrysanthemum morifolium cv. ‘Resomee Splendid’

Abstract: BackgroundChrysanthemum; also commonly known as mums or chrysanths, is one of the most important ornamental crops worldwide. Introducing desirable traits into this valuable plant by the conventional breeding has so far been faced with some restrictions due to the limited gene pool and cross-incompatibility. Therefore, breeders have decided to exploit Agrobacterium-mediated transformation methods in order to satisfy the growing market demands. However, more efficient in vitro regeneration protocols are required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
2
8
0
1
Order By: Relevance
“…1). Similar findings were obtained in several studies using the identical groups of hormones (Xu et al 2012, Naing et al 2014, Kazeroonian et al 2018.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…1). Similar findings were obtained in several studies using the identical groups of hormones (Xu et al 2012, Naing et al 2014, Kazeroonian et al 2018.…”
Section: Resultssupporting
confidence: 90%
“…Addition of cytokinin in the regeneration medium generally increases shoot number per explant. Several previous reports have confirmed that BAP accelerates the development of the shoot buds as well as enhancing the shoot primordial development in chrysanthemum and in other plants (Lee et al 1997, Yesmin et al 2014, Kazeroonian et al 2018). Among the nine treatments tested T6 produced highest mean number of shoot/explant 8.67 and 7.67 for Y and BARI Chry-2 variety, respectively.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…11 However, shoots were formed directly in the leaf explants of Chrysanthemum morifolium on the media supplemented with BAP. 18 In contrast, leaf segments of S. viarum did not induce any shoot with BA. 11 Adventitious shoots were also obtained in Titanotrichum oldhamii using medium supplemented with 0.1mg/L BA.…”
Section: Bap Alone or In Combination With Iba Influenced Direct Organogenesis In Leaf Lamina Leaf With Petiole And Petiole Explants Of Inmentioning
confidence: 92%
“…Theo nghiên cứu trước đây, tái sinh chồi bất định từ mẫu lá thường được thực hiện bằng cách bổ sung auxin kết hợp với cytokinin, cụ thể nồng độ auxin cao hơn so cytokinin, sẽ tốt cho quá trình tái sinh chồi. Theo Kazeroonian et al (2018), sử dụng 4,5 mg/l BAP kết hợp 1,0 mg/l NAA, chồi được tái sinh trực tiếp từ mảnh lá, cho số chồi trung bình/mẫu đạt 2,06 chồi/mẫu sau 7 tuần [15], trong khi nghiên cứu của chúng tôi cho thấy, môi trường tái sinh chồi trực tiếp từ lá khá đơn giản, chỉ cần bổ sung BAP 0,50 mg/l, chồi được tái sinh trực tiếp từ mảnh lá sau 5 tuần và cao hơn.…”
Section: Nồng độ Bap (Mg/l)unclassified